الأديان الشرقية المنتسبة إلى الفكر الهندوسي وعلاقتها بالإسلام في مبادئ الأخلاق والسلوك: Eastern religions affiliated with Hindu thoughts and their relationship with Islam in the principles of ethics and behaviours - Huda, Muhammad Nazmul (Al Manhal Research Journal, 2024)
Abstract: Eastern religions affiliated with Hindu thought include several religious movements and philosophies that originated in the Indian subcontinent, such as Hinduism, Buddhism, Jainism, and Sikhism, and have profound influences on the culture and spirituality of South Asia. Islam is another religion that has had a significant impact on the people of this region. These religions share the principles of Islam in many aspects of morality and behaviours. However, there is no accurate study of these wonderful commonalities between these religions and Islam. This study attempts to find the relationship between Eastern religions affiliated with Hindu thought and Islam in the aspects of morality and behaviours. The researcher relied on the descriptive and analytical approach, by collecting information from its sources, and trying to analyze it to reach the desired results. The discussion was concluded with some of the results and recommendations reached by this study. Keywords: Hinduism, Buddhism, Sikhism, Jainism, Maharishi, Ethics and Behavior.